Comparison of procedural outcomes in patients undergoing catheter vs surgical ablation for atrial fibrillation and heart failure with reduced ejection fraction. Issue 1 (23rd November 2020) - Doshi, Rajkumar; Kumar, Ashish; Shariff, Mariam; Adalja, Devina; Patel, Krunalkumar; Patel, Kirtenkumar; Desai, Rupak; Gullapalli, Nageshwara; Vallabhajosyula, Saraschandra
Abstract: Background: There is a lack of research comparing procedural outcomes of surgical ablation (SA) and catheter ablation (CA) among patients with heart failure with reduced ejection fraction (HFrEF) and atrial fibrillation (AF). The main objective was to compare the short‐term procedural outcomes of SA and CA in patients with HFrEF. Methods: We used the national inpatient sample to identify hospitalizations over 18 years with HFrEF hospitalization and AF, and undergoing SA and CA from 2016 to 2017. Furthermore, the clinical outcomes of SA vs CA in AF stratified as nonparoxysmal and paroxysmal were analyzed. Results: A total of 1, 770 HFrEF hospitalizations with AF who underwent SA and 1, 620 HFrEF hospitalizations with AF who underwent CA were included in the analysis. Hospitalizations with CA had higher baseline comorbidities. The in‐hospital mortality among HFrEF with AF undergoing SA as compared with CA was similar (2.8% vs 1.9%, respectively, adjusted P‐value 0.09). Hospitalizations with SA had a significantly longer length of hospital stay, a higher percentage of postprocedural, and cardiac complications. In HFrEF hospitalizations with nonparoxysmal AF, SA as compared with CA was associated with a higher percentage of in‐hospital mortality (2.4% vs 1%, adjusted P ‐value <.05), a longer length of stay, a higher cost of treatment, and a higher percentage of cardiac complications. Conclusion: CA is associated with lower in‐hospital adverse procedural outcomes as compared with SA among HFrEF hospitalizations with AF. Further research with freedom from AF as one of the outcome is needed between two groups for HFrEF. Abstract : Catheter ablation is associated with lower in‐hospital procedural outcomes as compared to surgical ablation among heart failure with reduced ejection fraction hospitalizations. The recurrence of atrial fibrillation, long‐term safety, efficacy, and quality of life associated with surgical and catheter ablation remain to be determined in this population.